ANALISIS KEARIFAN LOKAL MELALUI KAJIAN FOLKLOR ASAL USUL KOTA LANGSA - R. Ramazan; Mufti Riyani (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
This study aims to draw a link between various versions or variants in the folklore of Langsa City to obtain local wisdom content that is intended to be utilized to strengthen the identity of the Langsa City community as a plural society. The method uses a qualitative approach with descriptive research types and field studies. This research consists of three stages, namely documenting or collecting data, classifying or classifying and analyzing. The main data was obtained directly by researchers through interviews with informants and observations with natural settings. In collecting research data, several kinds of methods are used, namely observation, interviews, literature study and documentation. Data analysis in qualitative research is carried out during data collection and after completing data collection within a certain period.The results of the folklore analysis With the majority of its classification as oral folklore. The folklore of Langsa city origin can be analyzed from the approach of language, background of toponim and development of the form of folklor. The implementation of local wisdom in the cultural and social system is found in local wisdom meulaot, peulara uteun and duek pakat.